Enhancement the Antimicrobial Activity of Disinfectants by the Purified Lipase from Coronobacter Dublinensis - Alaa Naseer Mohammed Ali1, Sahira Nsayef Muslim2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
There are many different commercial disinfectants purchased, choosing of effective product is a prime target to ensure its decontamination efficiency. Thus we screened Coronobacter dublinensis isolates to produce lipase enzyme with using of vegetable oil like olive oil as inducer of lipase production in the medium. The lipase was purified by using two-step purification procedure consisting of ethanol precipitation and ion exchange chromatography with a yield of 48.3%. The lipase has an important role in enhancement of disinfectant activity. Since the combination between this disinfectant and lipase led to increase the activity of disinfectant to higher levels and the width of inhibition area enlarged to 28 mm against Acinetobacter sp. followed by P. aeruginosa and S. aureus with 25mm, respectively. So that we can conclude that lipase has excellent activity for enhancement of the commercial disinfectants purchased in decontamination activities in the laboratory and hospital environments.